Cutaneous plasmacytosis Characterized by Head Plaques: An Unusual Case Report of a 57-Year-Old Male - Wei L; Zhang J; Di D; Wang D; Luo G (Dove Medical Press, 2023)
Lu Wei,* Jialin Zhang,* Dake Di, Dongmei Wang, Guangpu Luo Department of Traditional Chinese Medicine Dermatology, Dermatology Hospital of Southern Medical University, Guangzhou, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Guangpu Luo; Dongmei Wang, Department of Traditional Chinese Medicine Dermatology, Dermatology Hospital of Southern Medical University, No. 2, Lujing Road, Yuexiu District, Guangzhou City, Guangdong Province, 510091, People's Republic of China, Tel +86 13926166004 ; +86 13431086997, Fax +86-20-87257353, Email 102931@163.com; wongdongmei@163.comAbstract: Cutaneous plasmacytosis (CP) is a rare disorder of uncertain etiology. We report an unusual and rare case of CP in a 57‑year‑old male who presented with popular nodules all over the body, accompanied by head plaques. Pathological biopsy of the skin revealed large infiltration of mature plasma cells within the dermis. Elevated serum IgG4 concentrations were found. Immunohistochemical analysis confirmed the polyclonal nature of the plasma cells. The diagnosis of CP was established. Steroid therapy was administered at a dose of 20 mg/day. After 1 month of treatment, the patient's eruption showed regression. These findings remind dermatologists to include CP in their clinical differential diagnosis of patients with head plaques. Meanwhile, clinicians should carefully that individuals diagnosed with CP at risk for malignant transformation.Keywords: cutaneous plasmacytosis, IgG4-related disease, plasma cell, IgG4